Performa bank syariah di Indonesia pasca pandemi: Analisis peluang dan tantangan - Adinugroho, Muhammad Bayu (Maliki Interdisciplinary Journal, 2024)
Islamic banking as one of the important role holders in the Indonesian economic sector must be quick to recover in the face of all possibilities including pandemics. This study was conducted to determine how Islamic banking performs after the Covid-19 pandemic by considering the opportunities and challenges faced by Islamic banking. The data analysis technique uses previous research analysis with the results showing that based on the analysis of CAR, ROA, BOPO, FDR, NPF, and KAP ratios, the development of total assets and also the development of customers or users of Islamic banks in Indonesia after the Covid-19 pandemic shows a positive performance.